The oil-producing characteristics of Bang-Bang control for 2D reservoir. (November 2019) - Ma, Yinfei; Shi, Anfeng; Wang, Xiaohong
Abstract: The Bang-Bang control is one of the primary control methods to increase the cumulative oil production for water-flooding reservoir. The on-off state and operating time of the injection wells are adjusted to enhance the efficiency. In this article, the oil-producing characteristics of Bang-Bang control for optimization problems of 2D reservoir is studied. The efficiency of Bang-Bang control in different stages during the whole oilfield development process has been concluded. The regularity of the Bang-Bang control's strategy is summarized. The numerical simulation results show that, in early stage of oilfield development, Bang-Bang control may be the optimal solution amongst two-segment regulation strategies. In middle period, Bang-Bang control gains less oil production than the simultaneous optimization scheme. In high water-cut period, Bang-Bang control's oil production is approaching simultaneous scheme. For Bang-Bang control's optimal strategies, according to the distance between the production well and injection well, the farther injection well is supposed to open first, then it will be closed and nearer well will open to operate in the next segment. With the total production time become longer, the proportion of farther well's operating time will increase and stabilize at certain value finally. For engineering practice, it indicate that the optimal regulation strategies need to be formulated according to reservoir's development stages in order to improve the efficiency of oil production.